Acute appendicitis located within Amyand’s hernia—a complex case with concurrent acute cholecystitis - O’Connor, Adam (J Surg Case Rep, 2020)
Amyand’s hernia is the presence of the vermiform appendix within an inguinal hernia sac. It is rare, and even rarer is the presence of acute appendicitis within the sac. It presents in a variety of different ways and often is only diagnosed intra-operatively. We present the case of a 90 year old male with extensive co-morbidities presenting with right upper quadrant pain, who on computed tomography scan of the abdomen, had acute cholecystitis alongside acute appendicitis within Amyand’s hernia. Ultimately given his co-morbidities, a conservative approach with prolonged antibiotic therapy was adopted, with a successful outcome. This case highlights that although classifications for treatment of Amyand’s hernia exist, careful clinical assessment is warranted in each case to ensure optimal outcome based upon individual circumstances.